Low serum miR‐223 expression predicts poor outcome in patients with acute myeloid leukemia. Issue 3 (6th November 2019) - Yu, Guopan; Yin, Zhao; He, Han; Zheng, Zhongxin; Chai, Yanyan; Xuan, Li; Lin, Ren; Wang, Qiang; Li, Jie; Xu, Dan
Abstract: Background: Identification of biomarkers for acute myeloid leukemia (AML) is important for treating this malignancy. Recent studies have reported that microRNAs (miRNAs) are stably detectable in the blood/plasma and can be used as biomarkers for various types of cancer including AML. The aim of this study was to analyze miR‐223 level in serum as a potential indicator for AML diagnosis and prognosis prediction. Methods: Quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was used to detect the levels of miR‐223 in the serum samples from 131 patients and 70 healthy individuals. Results: The results revealed that serum miR‐223 was underexpressed in AML patients, particularly those in intermediate and unfavorable cytogenetic risk groups. Further analysis revealed that serum miR‐223 could yield a receiver operating characteristic (ROC) area under the curve (AUC) of 0.849 with 83.2% sensitivity and 81.4% specificity. Moreover, a significant increase in serum miR‐223 level was observed in AML subjects after their treatment. Reduced serum miR‐223 level was highly associated with aggressive clinical variables and shorter survival of patients. Furthermore, miR‐223 expression was identified to be an independent prognostic predictor of worse overall survival. Conclusion: In conclusion, miR‐223 may be a reliable diagnostic and prognostic biomarker for AML.